Let α and β be the roots of the equation x 2 + x − 3 = 0 such that α < β . Find the value of the expression 4 β 2 − α 3 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution buddy! B)
x 2 − x , just trying latex, dont worry
Log in to reply
That command is to be used like this
\require{cancel} \cancel{x}
Which will give
x
'\require{cancel}' command is important here.
Moreover
\require{cancel} \cancel{x}^1
will give
x 1
and
\require{cancel} \cancel{x}_1
will give
x 1
BRUTE FORCE SOLUTION
By the quadratic formula, the roots of x 2 + x − 3 , which will be denoted by α and β , where α < β , are
α β = 2 − 1 − 1 3 = 2 − 1 + 1 3 .
So,
4 β 2 − α 3 = 4 × 4 ( − 1 + 1 3 ) 2 − 8 ( − 1 − 1 3 ) 3 = ( − 1 + 1 3 ) 2 − 8 ( − 1 − 1 3 ) 3 .
Observe that
( − 1 + 1 3 ) 2 ( − 1 − 1 3 ) 3 = 1 4 − 2 1 3 = ( 1 4 + 2 1 3 ) ( − 1 − 1 3 ) = − 4 0 − 1 6 1 3 = − 8 ( 5 + 2 1 3 ) .
As a result,
4 β 2 − α 3 = 1 4 − 2 1 3 − 8 − 8 ( 5 + 2 1 3 ) = 1 4 − 2 1 3 + 5 + 2 1 3 = 1 9 ,
as required.
Its quire tough to do it like this
Log in to reply
Brute force solutions may not be the best way of arriving to solutions to many people, but it is a foolproof way of proving things. If you take issue with it, that's your issue, not mine's.
From Vieta's Theorem, we get
β + α = − 1
β α = − 3
And then, because α < β , so
β − α = Discriminant
β − α = ( − 1 ) 2 − 4 . 1 . ( − 3 )
β − α = 1 + 4 . 3 = 1 3
Now, let
x = 4 β 2 − α 3 , and
y = 4 α 2 − β 3
Now
(1)...
x + y = 4 β 2 − α 3 + 4 α 2 − β 3 x + y = 4 ( β 2 + α 2 ) − ( α 3 + β 3 ) x + y = 4 ( ( β + α ) 2 − 2 β α ) − ( α + β ) ( α 2 − β α + β 2 ) x + y = 4 ( ( − 1 ) 2 − 2 ( − 3 ) ) − ( − 1 ) ( ( α + β ) 2 − 3 α β ) x + y = 4 ( 1 + 2 . 3 ) + ( ( − 1 ) 2 − 3 ( − 3 ) ) x + y = 4 . 7 + ( 1 + 3 . 3 ) = 2 8 + 1 0 = 3 8
And then
(2)...
x − y = 4 β 2 − α 3 − 4 α 2 + β 3 x − y = 4 ( β 2 − α 2 ) + ( β 3 − α 3 ) x − y = 4 ( β + α ) ( β − α ) + ( β − α ) ( α 2 + β α + β 2 ) x − y = 4 ( ( − 1 ) ( 1 3 ) + ( 1 3 ) ( ( α + β ) 2 − α β ) x − y = − 4 1 3 + 1 3 ( ( − 1 ) 2 − ( − 3 ) ) x − y = − 4 1 3 + 1 3 ( 1 + 3 ) = − 4 1 3 + 4 1 3 = 0
Now, we find the value of x .
(1)+(2)
x + y + x − y = 3 8 + 0 2 x = 3 8 x = 1 9 4 β 2 − α 3 = 1 9
Let suppose for a general quadratic a x 2 + b x + c = 0 whose roots are α and β with α < β , so we have
β = 2 a − b + b 2 − 4 a c α = 2 a − b − b 2 − 4 a c ⟹ β − α = 2 ( 2 a b 2 − 4 a c ) = a Discriminant
But as in the third step of your solution, you've simply stated β − α = Discriminant which may give a false information to someone reading your solution who doesn't have a good understanding of quadratics yet.
Problem Loading...
Note Loading...
Set Loading...
By Vieta's formula, we have
α + β = − 1
Note that
4 β 2 − α 3 = 4 ( − 1 − α ) 2 − α 3 = − α 3 + 4 α 2 + 8 α + 4 = − α ( α 2 + α − 3 ) 0 + 5 = 3 ( α 2 + α ) + 4 = 5 ( 3 ) + 4 = 1 9